Pengaruh Implementasi Visi dan Misi Sekolah Dalam Proses Pembelajaran Terhadap Kinerja Guru Di Mts Qaryatul Jihad Pondok Kubang Bengkulu Tengah - Achmad Novan Safi’I; Khairiah; Masrifa Hidayani (JPT : Jurnal Pendidikan Tematik, 2025)
The purpose of this study is to determine the factors that influence the implementation of the school's vision and mission in the learning process and teacher performance. This study employed a survey with quantitative methods. Data collection techniques used included observation, questionnaires, and documentation. The sample consisted of all teachers at MTs Qaryatul Jihad, Pondok Kubang Village, Pondok Kubang District, Central Bengkulu Regency. The results indicate that the implementation of the vision and mission at MTs Qaryatul Jihad, Pondok Kubang Village, Pondok Kubang District, Central Bengkulu Regency, can be categorized as high, with a score of 48, ranging from 46.47 to 60.